Predictive Power Control of Grid and Rotor Side converters in Doubly Fed Induction Generators Based Wind Turbine - Abdelmalek Boulahia; Mehdi Adel; Hocine Benalla (Bulletin of Electrical Engineering and Informatics, 2013)
This paper presents a new control scheme for grid and rotor side for doubly fed induction generator (DFIG) using model based predictive control. The control strategy minimizes quality functions, which represent the desired behavior of the converter. The technique developed uses predictive direct power control to control the rotor and grid side converter. The main advantages of this method are no need of linear controllers, coordinates transformations or modulators for converter and inverter. Simulation results demonstrate robust, precise, and fast dynamic behavior of system.